Trends in excess male mortality in the working age population in a region with the highest mortality rates in Poland - Beata Ciabiada-Bryła; Małgorzata Pikala; Monika Burzyńska; Wojciech Drygas; Irena Maniecka-Bryla (Nofer Institute of Occupational Medicine, 2020)
Background The intensity of premature deaths in the Łódź region in 2014 amounted to 40 per 10 000, and was the highest in the country (the average rate for Poland was 32). Excess mortality of men aged <65 continues to be a major medical and social problem. The aim of the study is to analyze time trends of excess male mortality in the working age population in the Łódź region, both in general and due to the most important causes of deaths. Material and Methods The research material consists of information on 144 589 deaths of the Łódź region inhabitants aged 20-64 in 1999-2014. Crude and standardized mortality rates were calculated, as well as excess male mortality rates both in general and by cause of death. Standardization was carried out using the direct method according to the standard European population. A study of time trends was performed with the use of the joinpoint regression analysis. Average annual percentage rates of changes were estimated. Results The excess mortality rate of men at the productive age decreased from 2.9 to 2.8 in the Łódź region in 1999-2014. The most important causes of death among men aged 20-64 in 2014 were (rates per 10 000): cardiovascular diseases (19.1), malignant neoplasms (16.6) and external causes of death (12.3). Among women, the most significant were malignant neoplasms (11.1), cardiovascular diseases (5.1) and diseases of the digestive system (2.1). The excess mortality rate of men aged 20-64 in the analyzed period reached the highest values due to external causes of death (5.1-7.3) and cardiovascular diseases (3.0-3.7). The highest rate of the decline in excess male mortality in 1999-2014 was recorded due to malignant neoplasms, on average 1.4% per year (p < 0.05). Meanwhile, the fastest growth concerned external causes of death, on average 1.0% per year (p < 0.05). Conclusions Despite the decline in the mortality rates among both sexes, excess male mortality due to external causes of death and cardiovascular diseases increased. Med Pr. 2020;71(3):325-35